The Effect of Business Firms' International Activities on the Firm Performance: A Central Black Sea Region Case - ALTINDAG, Erkut; KARKACIER, Merve (International Review of Management and Marketing, 2014)
In this study, the effect of business firms carrying on business in Central Black Sea Region of Turkey on the performance of these firms. Especially how it affected SMEs (Small and Medium Sized Enterprises) was analyzed. When particularly considering the effects of business that have SME quality on economy of Turkey, such kind of researches are noticed to have a basis in recent years. The research depended upon the data obtained from enterprises through original qualified questionnaire. The questionnaire question forms were scaled benefiting from the studies in the literature based upon international activities and business performance measurement. For all variables, the scales in the literature were taken and included into research questionnaire. The questionnaires were performed to SMEs and large-scale enterprises. In the research factor analysis, correlation and regression analysis were included as analysis methods. According to the obtained results, it was determined that international activities had a positive effect on the performance of enterprises. The results were interpreted, and various suggestions were offered to academicians, and administrators. Keywords: International Activities; Import and Export; Franchising; Joint Ventures; Firm Performance JEL Classifications: M10; M16